A review of contractor selection methods in Iceland : risky business? - Björg Brynjarsdóttir 1990- (2017)
It has long been recognised that poor quality, delays and cost overruns are common in the construction industry due to reasons that have often been linked to the unpredictable nature of the industry. However, even though many factors can contribute to project failure one of the most influential factors affecting a projects' outcome is the selection of a contractor in the pre-construction phase. The combination of frequent cost overruns in Icelandic public projects, recent news about tax evasion, human trafficking and shortcomings regarding safety in the Icelandic construction industry have led to the impression that the methods used by Icelandic organizations impose too much risk and need to be reviewed. The overall aim of this study was to understand the contractor selection methods applied by Icelandic organisations, compare them to those recommended by experts, and conclude if the methods used impose too much risk for organisations. In an attempt to explore the topic an extensive literature review was conducted, semi-structured interviews were held with a small sample of construction industry professionals, and an e-mail questionnaire survey of 1378 Icelandic organizations was sent out. The results indicate that Icelandic organisations use multiple criteria selection to some extent but price is the most important criteria. The criteria most frequently used are professional knowledge, experience of a similar project, and whether the contractor has worked for the organisation before. Other criteria, such as financial stability of contractors, their health & safety policy, and whether they work in accordance with a certified quality management system - have a much lower weigh in the selection process. These results indicate that the methods used are somewhat lacking and that there is ample room for improvement in order to minimize risk. Gæðavandamál, tafir og hár kostnaður eru þekkt í byggingariðnaðinum og hefur skuldinni oft verið skellt á óútreiknanlegt eðli iðnaðarins. Víst er að margt getur haft áhrif ...